Preference for Exercise vs. More Sedentary Reinforcers: Validation of an Animal Model of Tetrabenazine-Induced Anergia - Carratalá-Ros, Carla; López-Cruz, Laura; SanMiguel, Noemí; Ibáñez-Marín, Patricia; Martínez-Verdú, Andrea; Salamone, John D.; Correa, Mercè (Frontiers in Behavioral Neuroscience, 2020)
Physical activities can have intrinsic motivational or reinforcing properties. The choice to engage in voluntary physical activity is undertaken in relation to the selection of other alternatives, such as sedentary behaviors, drugs or food intake. The mesolimbic dopamine (DA) system plays a critical role in behavioral activation or exertion of effort, and DA antagonism or depletion induces anergia in effort-based decision-making tasks. However, little is known about the neural mechanisms underlying the decision-making processes that establish preferences for sedentary versus activity-based reinforcers. In the present work with male CD1 mice, we evaluated the effect of tetrabenazine (TBZ), a DA depleting agent, on a 3-choice-T-maze task developed to assess preference between reinforcers with different behavioral activation requirements and sensory properties (i.e., a running wheel (RW) vs. sweet pellets or a neutral non-social odor). We also studied the effects of TBZ on the forced swim test (FST), which measures climbing and swimming in a stressful setting, and on anxiety tests (dark-light box; DL, and elevated plus maze; EPM). In the 3-choice task, TBZ reduced time running in the wheel but increased time spent consuming sucrose, thus indicating reduced activation but relatively intact sucrose reinforcement. The effect of TBZ was not mimicked by motivational manipulations that change the value of the reinforcers, such as making the RW aversive or harder to move, food-restricting the animals, inducing a binge-like eating pattern, or introducing social odors. In the FST, TBZ decreased time climbing (most active behavior), and increased immobility, but did not affect anxiety in the DL or EPM. These results indicate that the 3-choice-T-maze task could be useful for assessing DA modulation of preferences for exercise based on activation and effort requirements, differentiating those effects from changes in preference produced by altering physical requirements, food-restriction state, and stress during testing.